Possible endocannabinoid control of colorectal cancer growth - Ligresti, Alessia; Bisogno, Tiziana; Matias, Isabel; De Petrocellis, Luciano; Cascio, Maria Grazia; Cosenza, Vittorio; D'argenio, Giuseppe; Scaglione, Giuseppe; Bifulco, Maurizio; Sorrentini, Italo; Di Marzo, Vincenzo (Gastroenterology (New York, N.Y. 1943), 2003)
The endocannabinoids anandamide and 2-arachidonoylglycerol (2-AG) inhibit cancer cell proliferation by acting at cannabinoid receptors (CBRs). We studied (1). the levels of endocannabinoids, cannabinoid CB(1) and CB(2) receptors, and fatty acid amide hydrolase (FAAH, which catalyzes endocannabinoid hydrolysis) in colorectal carcinomas (CRC), adenomatous polyps, and neighboring healthy mucosa; and (2). the effects of endocannabinoids, and of inhibitors of their inactivation, on human CRC cell proliferation. Tissues were obtained from 21 patients by biopsy during colonoscopy. Endocannabinoids were measured by liquid chromatography-mass spectrometry (LC-MS). CB(1), CB(2), and FAAH expression were analyzed by RT-PCR and Western immunoblotting. CRC cell lines (CaCo-2 and DLD-1) were used to test antiproliferative effects. All tissues and cells analyzed contain anandamide, 2-AG, CBRs, and FAAH. The levels of the endocannabinoids are 3- and 2-fold higher in adenomas and CRCs than normal mucosa. Anandamide, 2-AG, and the CBR agonist HU-210 potently inhibit CaCo-2 cell proliferation. This effect is blocked by the CB(1) antagonist SR141716A, but not by the CB(2) antagonist SR144528, and is mimicked by CB(1)-selective, but not CB(2)-selective, agonists. In DLD-1 cells, both CB(1) and CB(2) receptors mediate inhibition of proliferation. Inhibitors of endocannabinoid inactivation enhance CaCo-2 cell endocannabinoid levels and block cell proliferation, this effect being antagonized by SR141716A. CaCo-2 cell differentiation into noninvasive cells results in increased FAAH expression, lower endocannabinoid levels, and no responsiveness to cannabinoids. Endocannabinoid levels are enhanced in transformed colon mucosa cells possibly to counteract proliferation via CBRs. Inhibitors of endocannabinoid inactivation may prove useful anticancer agents.